2021
DOI: 10.1177/10731911211046661
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Severity of Preschool-Aged Children’s Internalizing Behaviors: A Daily Diary Analysis

Abstract: A subset of preschool-aged children meets criteria for impairing and persistent anxiety and depression. However, the overlap between normative emotional development and impairing symptoms complicates assessments of internalizing problems in early childhood. Given the benefits of early identification/prevention and avoiding overpathologizing typical development, empirical information is needed to norm expression of internalizing behaviors. In this 14-day online diary study, 609 primary caregivers of 3- to 5-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 111 publications
(132 reference statements)
2
6
0
Order By: Relevance
“…Using daily diary reports of objective frequency of behavioral occurrence to differentiate typical and atypical manifestations of internalizing behaviors in early childhood, they are the first to characterize the dimensional spectrum of these behaviors. Consistent with our prior work in the disruptive behavior domain (Wakschlag et al., 2014), they have demonstrated that differentiation of typical:atypical internalizing behaviors can be modeled along a severity continuum (Bufferd et al., 2023), and can be distinguished in terms of frequency of occurrence (which varies based on the nature of behavior) and context (Bufferd et al., 2017, 2019).…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…Using daily diary reports of objective frequency of behavioral occurrence to differentiate typical and atypical manifestations of internalizing behaviors in early childhood, they are the first to characterize the dimensional spectrum of these behaviors. Consistent with our prior work in the disruptive behavior domain (Wakschlag et al., 2014), they have demonstrated that differentiation of typical:atypical internalizing behaviors can be modeled along a severity continuum (Bufferd et al., 2023), and can be distinguished in terms of frequency of occurrence (which varies based on the nature of behavior) and context (Bufferd et al., 2017, 2019).…”
Section: Introductionsupporting
confidence: 83%
“…This advances application of the science of "when to worry" framework to young children's anxious and depressive behaviors. As we and others have noted (Bufferd et al, 2023;Wakschlag et al, 2018), thresholds of risk vary based on the nature of the behavior. This is also demonstrated across the multiple cross-age papers in this special issue validating the MAPSL-TL Infant-Toddler and Youth versions (Alam et al, 2023;Hirsch et al, 2023;Kirk et al, 2023;.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations